New records of Hipposideros griffini from lava caves and the threats to its conservation in Vietnam - Thong, Vu Dinh (Academia Journal of Biology, 2019)
Lava caves are unique and fragile ecosystems which are suitable for a wide variety of plant and animal species. However, the biodiversity of lava caves is still poorly studied. To increase knowledge of these special ecosystems, several rapid surveys on bats were carried out in Dak Nong Province in sounthern Vietnam between 2014 and 2019. Bats were captured in the field using mist nets and harp traps. Echolocation calls were recorded in different situations using the PCTape system. The results include records of Griffin’s leaf-nosed bat (Hipposideros griffini) which is regarded as a species endemic to Vietnam only. Prior to the present study, it was only recorded from karst and moutain habitats in three different regions of Vietnam: Cat Ba National Park in the northeast, Chu Mom Ray in the central highlands, and Cat Tien National Park in the southeast. Records of Hipposideros griffini from Dak Nong Province extend its distributional range and highlight the importance of lava cave systems for biodiversity research and conservation in Vietnam. Griffin’s leaf-nosed bat and other animal species inhabiting the lava caves have been critically threatened by hunting and other human activities. Morphological measurements and echolocation calls of Hipposideros griffini together with the threats to its conservation status in Dak Nong Province are given in this paper.